2017
DOI: 10.1016/j.tra.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

A stated choice experiment to measure the effect of informational and normative conformity in the preference for electric vehicles

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International licence Newcastle University ePrints-eprint.ncl.ac.uk Cherchi E. A stated choice experiment to measure the effect of informational and normative conformity in the preference for electric vehicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 50 publications
5
67
0
Order By: Relevance
“…Informational and social conformity appear highly significant mechanisms influencing individual EV over ICV decision making in a recent Danish experimental research (Cherchi, ). This is consistent with Norwegian data comparing EV and ICV owners (Figenbaum et al, ), ICV owners with EV owning friends were much more likely to consider buying an EV than ICV owners without such friends.…”
Section: Factors Affecting Consumer Decision Makingmentioning
confidence: 96%
“…Informational and social conformity appear highly significant mechanisms influencing individual EV over ICV decision making in a recent Danish experimental research (Cherchi, ). This is consistent with Norwegian data comparing EV and ICV owners (Figenbaum et al, ), ICV owners with EV owning friends were much more likely to consider buying an EV than ICV owners without such friends.…”
Section: Factors Affecting Consumer Decision Makingmentioning
confidence: 96%
“…Significant effects are found for financial policy measures (Hardman, Chandan, et al, 2017) which directly influence the internal factors of the car. Policy measures such as free parking (Cherchi, 2017;Fearnley, Pfaffenbichler, Figenbaum, & Jellinek, 2015;Hoen & Koetse, 2014) and access to HOV/Bus lines (Bjerkan et al, 2016;Chorus, Koetse, & Hoen, 2013) have provided mixed evidence in support of a positive effect on EV purchase intention.…”
Section: Ev Purchase Intentions and Charging Infrastructurementioning
confidence: 99%
“…In the first study only 12% or respondents recalled having seen a public charger and in the second study only 18%. More recently, Cherchi (2017) has taken into account charging infrastructure availability and other parking policies and found that availability did have a positive effect on purchase intention; this study however focussed on availability of charging infrastructure away from home. Ensslem, Jochem, Schäuble, & Babrowski (2013) also find that interoperability across charging station and borders, especially in border regions, is mentioned as an important factor driving purchase decisions.…”
Section: Ev Purchase Intentions and Charging Infrastructurementioning
confidence: 99%
“…Following some pilot testing, for the EV market share we decided to include both the total 139 number of new EV registration in 2019 in the UK and the percentage of new EV registered 140 compared to the total number of cars registered in the same year. This differed from our previous 141 work (Cherchi, 2017). We also decided to manipulate this information to give more emphasis to 142 the low and high penetration level.…”
Section: Introduction 44 45mentioning
confidence: 99%
“…Finally, a set of attitudinal questions was asked, measuring attitudes toward 190 environment and injunctive norms. The statements were taken from Cherchi (2017).…”
mentioning
confidence: 99%